High accuracy testbed for thermoelectric module characterization. (1st November 2020) - Guarnieri Calò Carducci, Carlo; Spadavecchia, Maurizio; Attivissimo, Filippo
Highlights: Presents an improved technique to characterize TE modules extensively. The setup was based on the use of thermistors and on a low number of components. A precise feedback control was implemented to set the temperature gradients. An uncertainty drop of two orders of magnitude in temperature-derived measurements. Abstract: In this paper, we present an improved version of the unified method (UM) for thermo-electric modules (TEM) characterization with the aim to reduce the overall parameters uncertainty. The parameters that make up the commonly accepted figure of merit Z or z T ¯ are mainly affected by temperature related uncertainty, which also significantly limit the precision of the test conditions and thus the reliability of derived models. To overcome these limitations, we conceived a novel and simplified measurement setup that relies at the same time on thermistor technology rather than thermocouple and on a lower number of required components. The improved setup, exploits a solid calibration procedure to reduce the uncertainty in temperature measurements from 1.4 °C typical of a J-type thermocouple (Class 1 IEC-EN 60584-2) to 0.027 °C with calibrated thermistors, leading to a previously unachievable millidegree-precision temperature control and to an uncertainty drop of two orders of magnitude in all the temperature-derived measurements. Such improvement has a direct feedback on both the α S and Θ, leading to a drop of a least one order of magnitude for a ΔT of 3 °C and more than 44 times for the latter at 30 °C. As result, the figure of merit z T ¯ can now be determined with an uncertainty equal to 0.58%.